2004
DOI: 10.1097/01.coc.0000128727.40450.9e
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Gemcitabine, Paclitaxel, Oxaliplatin Combination Chemotherapy in Patients With Cisplatin-Refractory Germ Cell Tumor

Abstract: Although the overall cure rate for advanced germ cell tumor (GCT) is high, the prognosis for patients with cisplatin-refractory GCT remains poor. Gemcitabine, paclitaxel, and oxaliplatin have shown significant activity as single agents in these patients. We investigated the activity and tolerance of a weekly gemcitabine, paclitaxel, oxaliplatin chemotherapy regimen. From September 2000 to February 2002, 9 patients with cisplatin-refractory GCT were treated with gemcitabine 800 mg/m2, paclitaxel 70 mg/m2, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hence our study populations were more likely to be homogenous. Other platinum-resistant carcinomas which have been treated with paclitaxel based salvage therapy include testicular [144][145][146][147] , NSCLC 148,149 , urothelial 150 , bladder 151 and endometrial carcinomas 152 .…”
mentioning
confidence: 99%
“…Hence our study populations were more likely to be homogenous. Other platinum-resistant carcinomas which have been treated with paclitaxel based salvage therapy include testicular [144][145][146][147] , NSCLC 148,149 , urothelial 150 , bladder 151 and endometrial carcinomas 152 .…”
mentioning
confidence: 99%
“…Interestingly, no excess neurotoxicity (2%) was observed despite the combination of two potentially neurotoxic drugs [23]. Although the two trials are not comparable, in the current study grade 3 and 4 neutropenia occurred in 22% and 15% of patients, respectively, and grade 3 and 4 ane- In contrast, in another small study from Italy, with the same drug combination given weekly (paclitaxel 70 mg/m 2 , LOHP 50 mg/m 2 and gemcitabine 800 mg/m 2 on days 1, 8 and 15 in cycles of 4 weeks) in nine cisplatin refractory germ-cell tumor patients the results were not as promising [24]. The authors concluded that the combination was not feasible in that heavily pretreated patient population due to excessive hematological toxicity, in particular severe thrombocytopenia (only one patient could continue the schedule) [24].…”
Section: Discussionmentioning
confidence: 85%
“…In these patients, clinical trials or treatment with agents such as gemcitabine, paclitaxel and oxaliplatin have been tested 87 . For patients with a good performance status and adequate bone marrow function, combination regimens of two of these new agents (e.g., gemcitabine plus oxaliplatin, gemcitabine plus paclitaxel) could be suggested, since at least a small percentage (5-15%) of patients may again reach long-lasting remissions [87][88][89][90] . Residual tumors after salvage chemotherapy should be resected within 4-6 weeks of marker normalization or when a marker plateau is reached.…”
Section: Relapsed/refractory Diseasementioning
confidence: 99%